PENGARUH REMUNERASI TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI SEBAGAI VARIABEL MEDIASI (Survei pada Pegawai Kantor Imigrasi Kelas I Surakarta) - Lamidi, Febyana Listya Sitinjak, Suprayitno & (Universitas Slamet Riyadi, 2016)
The purpose of this study is: to analyze the significance of the influence of remuneration against motivation, analyze the significance of the influence of remuneration on performance, analyzing the significance of the influence of motivation on performance and to analyze the significance of the influence of remuneration on performance that is mediated by the motivation on the immigration Clerk class I. Research methods method using survey data, the type of data used was qualitative and quantitative data, the source data used the primary data and secondary data. The population in this research is the entire Immigration clerk class I of Surakarta, that as many as 77 people. Technique of data analysis used the test of validity, reliability test, test the assumptions of classical, path analysis. Based on the research results obtained the conclusion that influence remuneration against motivation, influence remuneration against the performance of an employee, the influence of motivation on performance clerk retrieved the conclusion there is a significant influence. Other findings from the results of the analysis show that mediate the influence of remuneration motivation on performance clerk at the immigration Clerk class I.Keywords: remuneration, motivation, employee performance.